The Reality of Crisis management among public school principals in Hebron Governorate during the Corona pandemic - Abu Khayran, Ashraf Mohammad; Alarjan, Atef Mahmoud (Journal of Educational and Psychological Sciences, 2021)
This study aimed at researching the reality of crisis management among public school principals in the Hebron governorate during the Corona pandemic, and this study was conducted on all public-school principals and principals in the Hebron governorates in the second semester of the academic year 2020/2021 on a sample consisting of (281). As principals, the descriptive approach is used, whereby the study tool that relates to crisis management for government school principals in Hebron Governorate during the Corona pandemic was built: Reality and Obstacles, and the tool’s validity and stability were sure. The study found that the reality of crisis management among public school principals in the Hebron governorate during the Corona pandemic came to a large extent, and the existence of differences in the reality of crisis management among public school principals in the Hebron governorate during the Corona pandemic from the viewpoint of government school principals in the Hebron governorate depending on the educational qualification variable and in favor of the academic qualification Master and above, and according to the variable of the directorate and in favor of the Hebron district, and according to the school gender variable in favor of schools Females by averages. The study found that obstacles to crisis management among public school principals in Hebron Governorate during the Corona pandemic came to a large extent And based on the results of the study, the recommendation: Giving the school director greater powers so that he can cope with any crisis he faces through his work, and work to provide the teaching bodies with training, internet and computers to enable them to work on teaching students according to the distance education programs approved by the ministry, And the participation of school principals in drawing up plans in the directorates and at the level of the ministry, due to their good knowledge of the reality through the nature of their work.